HUBUNGAN KEPATUHAN DIET DENGAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS DI POLI PENYAKIT DALAM RUMAH SAKIT UMUM DAERAH dr. M. HAULUSSY AMBON - Siti Nurhidayati; Yuli Gres Kakiay (Pasapua Health Journal, 2020)
Introduction: Diabetes Mellitus (DM) is a group of symptoms that exist in a person caused by an increase in blood glucose levels as a result of a progressive decrease in insulin secretion. Dietary adherence of DM patients plays an important role in stabilizing blood glucose levels, while adherence itself is an important thing to be able to develop routines (habits) that can help sufferers follow a diet schedule. This study aims to determine the “Relationship of Diet Compliance with Blood Sugar Levels in Diabetes Mellitus Patients at the Internal Medicine Polyclinic at the Regional General Hospital dr. M. Haulussy Ambon. Method: This study uses a correlational quantitative research method with a cross sectional approach. In this study, the sampling technique used was Total Sampling with the number of respondents obtained, namely 34 people. The instrument used in this research is a questionnaire sheet. Data analysis using the Chi-Squere test. Results: this study showed that there was a relationship between dietary adherence and blood sugar levels in diabetes mellitus patients with a pvalue = 0.001 (<0.05). So it can be concluded that there is a significant relationship between dietary adherence and blood sugar levels in diabetes mellitus patients at the Internal Medicine Polyclinic at the Regional General Hospital dr. M. Haulussy Ambon. Suggestion: for patients as additional information for diabetes mellitus patients to be able to do dietary compliance in order to stabilize blood sugar levels and help the healing process.